Analysis of the economic benefits of dehydrated potato producers - white chuño and food security, Puno - Peru - Cruz-Lauracio, Juan; Flores-Lujano, Faustino; Ávila-Choque, Ronald (Gestionar: revista de empresa y gobierno, 2024)
The article analyzes the economic benefits for the producer of white chuño or tunta, determining their income and production costs; it describes the characteristics of tunta as a food for food security. The data come from a sample of 53 agricultural producers in Ilave–Puno-Peru, from 2022. The method is hypothetical-deductive, applies the microeconomic theory of economic benefits of a company, includes an econometric model of the Cobb-Douglas production function. First, it was identified that the optimal production quantity is 347.60 kg of tunta; second, the income generated from the sale of the product is S/4171.20, with a total cost of S/3438.56, obtaining an economic benefit of S/732.64, including the producer’s opportunity cost; the third conclusion is that the white chuño or tunta is a non-perishable dehydrated food, which can be stored for extended periods, from 5 years or more, preserving its nutritional components. The study demonstrates the economic viability of tunta production, showing a clear benefit after considering all costs involved, including the producer’s opportunity cost. Moreover, the durable and non-perishable nature of the white chuño highlights its potential as a sustainable food that can offer long-term food security, given its ability to preserve nutrients over extended periods. This combination of economic profitability and nutritional benefits makes tunta production an attractive option in contexts where food preservation is critical.